2010
DOI: 10.1097/wno.0b013e3181dfa9ca
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Mechanism for Latent (Fusion Maldevelopment) Nystagmus

Abstract: Latent nystagmus (LN) is the by-product of fusion maldevelopment in infancy. Because fusion maldevelopment--in the form of strabismus and amblyopia--is common, LN is a prevalent form of pathologic nystagmus encountered in clinical practice. It originates as an afferent visual pathway disorder. To unravel the mechanism for LN, we studied patients and nonhuman primates with maldeveloped fusion. These experiments have revealed that loss of binocular connections within striate cortex (area V1) in the first months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 66 publications
(90 reference statements)
4
51
2
2
Order By: Relevance
“…Besides FMNS, there were other findings, including interocular suppression, strabismus, and small vertical oscillations of the eyes, with the most necessary and sufficient factor being binocular decorrelation. [30] The mechanisms of all these findings may be the lack of connectivity and suppression of temporalward neurons of major visual areas V1, V2 (prestriate cortex), medial temporal (MT), and medial superior temporal (MST) of the cerebral cortex. [30,31] In the present study, we found a high deviation of vertical PEP in severe anisometropes without amblyopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides FMNS, there were other findings, including interocular suppression, strabismus, and small vertical oscillations of the eyes, with the most necessary and sufficient factor being binocular decorrelation. [30] The mechanisms of all these findings may be the lack of connectivity and suppression of temporalward neurons of major visual areas V1, V2 (prestriate cortex), medial temporal (MT), and medial superior temporal (MST) of the cerebral cortex. [30,31] In the present study, we found a high deviation of vertical PEP in severe anisometropes without amblyopia.…”
Section: Discussionmentioning
confidence: 99%
“…[30] The mechanisms of all these findings may be the lack of connectivity and suppression of temporalward neurons of major visual areas V1, V2 (prestriate cortex), medial temporal (MT), and medial superior temporal (MST) of the cerebral cortex. [30,31] In the present study, we found a high deviation of vertical PEP in severe anisometropes without amblyopia. The finding is consistent with the small vertical oscillations of primate models reported by Tychsen et al [30] In our opinion, the results indicate that in nonamblyopes, the deviation of vertical PEP is associated with the severity of anisometropia.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Nevertheless, the predominant model of INS posits that the degraded visual experience as a result of cataract during an early critical period induces an adaptive ocular motor response that leads to INS. 28,29 Because INS develops in the presence of multiple sensory system diseases, it has been hypothesized that INS may be the result of failure of a portion of the smooth pursuit system to calibrate its own internal gain during a critical period of development.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Nevertheless, the predominant model of INS posits that the degraded visual experience as a result of cataract during an early critical period induces an adaptive ocular motor response that leads to INS. 28,29 Because INS develops in the presence of multiple sensory system diseases, it has been hypothesized that INS may be the result of failure of a portion of the smooth pursuit system to calibrate its own internal gain during a critical period of development. 28,29 The results presented here, that is, that dense cataracts present during the first 5 years of life were associated with either FMNS or INS, suggests that each motor outcome is a result of its own critical combination of time, duration, and type of associated visual system perturbation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation